Synthesis and Biological Evaluation of New Isoxazolyl Steroids as Anti-Prostate Cancer Agents - Rudovich, Anton S; Peřina, Miroslav; Krech, Anastasiya V; Novozhilova, Maria Y; Tumilovich, Anastasia M; Shkel, Tatyana V; Grabovec, Irina P; Kvasnica, Miroslav; Mada, Lukáš; Zavialova, Maria G; Mekhtiev, Arif R; Jorda, Radek; et al. (International journal of molecular sciences, 2022)
Steroids with a nitrogen-containing heterocycle in the side chain are known as effective inhibitors of androgen signaling and/or testosterone biosynthesis, thus showing beneficial effects for the treatment of prostate cancer. In this work, a series of 3β-hydroxy-5-ene steroids, containing an isoxazole fragment in their side chain, was synthesized. The key steps included the preparation of Weinreb amide, its conversion to acetylenic ketones, and the 1,2- or 1,4-addition of hydroxylamine, depending on the solvent used. The biological activity of the obtained compounds was studied in a number of tests, including their effects on 17α-hydroxylase and 17,20-lyase activity of human CYP17A1 and the ability of selected compounds to affect the downstream androgen receptor signaling. Three derivatives diminished the transcriptional activity of androgen receptor and displayed reasonable antiproliferative activity. The candidate compound, 24j (17R)-17-((3-(2-hydroxypropan-2-yl)isoxazol-5-yl)methyl)-androst-5-en-3β-ol, suppressed the androgen receptor signaling and decreased its protein level in two prostate cancer cell lines, LNCaP and LAPC-4. Interaction of compounds with CYP17A1 and the androgen receptor was confirmed and described by molecular docking.
Keywords: androgenní receptory; Steroids; Steroid 17-alpha-Hydroxylase; Male; protinádorové látky; Cell Line, Tumor; LAPC-4; isoxazoles; Prostatic Neoplasms; mužské pohlaví; steroid-17-alfa-hydroxylasa; Molecular Docking Simulation; molecular docking; Weinreb amide; prostate cancer; simulace molekulového dockingu; androgen signaling; lidé; Humans; nádory prostaty; LNCaP; androgen receptor; steroidy; nádorové buněčné linie; CYP17A1; Antineoplastic Agents; Receptors, Androgen